УСПЕХ В ОЦЕНОЧНОМ ДИСКУРСЕ ПРЕДПРИНИМАТЕЛЬСТВА - ПРОЦЕНКО, А. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
УСПЕХ В ОЦЕНОЧНОМ ДИСКУРСЕ ПРЕДПРИНИМАТЕЛЬСТВА В статье рассмотрена роль успеха в предпринимательской деятельности. Проанализированы возможности успеха как варианта оценочного суждения, интенсифицирующего деятельность субъекта предпринимательства в различные исторические эпохи, и направленность на дидактику с целью совершенствования его инновационной активности. Проценко О.О. УСПІХ В ОЦІННОМУ ДИСКУРСІ ПІДПРИЄМНИЦТВА В статті розглянута роль успіху у підприємницької діяльності. Проаналізовані можливості успіху як оцінного судження, який інтенсифікує творчу активність суб’єкту підприємництва в різні історичні епохи, та створює дидактичний напрямок з метою удосконалення Інноваційну соціальну активність. Ключові слова: підприємництво, успіх, дискурс, особистість, діяльність Protsenko A. SUCCESS IN THE ESTIMATING DISCOURSE OF BUSINESS UNDERTAKING The article deals with the role of success in business undertaking. The article also analizes the possibility of success as estimating opinion, that increases the activity of subject of business undertaking in different historical times and creates a didactica direction for improvement of innovating social activity. Key words: business undertaking, success, discourse, personality, activity.